A unique way to treat Goodpasture's disease. (24th November 2014) - Narayanan, Maya; Casimiro, Isabel; Pichler, Raimund
Abstract : A 21-year-old man with no medical history presented to the emergency department with fatigue, oliguria and lower extremity oedema. Initial laboratory tests showed that the patient was in acute renal failure with a creatinine of 12.8 mg/dL (normal 0.51–1.18 mg/dL). Further work up showed crescentic glomerulonephritis on renal biopsy, and serology was positive for antiglomerular basement antibody (titre 191 U/mL, normal 0–0.7 U/mL). Shortly after diagnosis he developed haemoptysis and chest imaging was consistent with pulmonary haemorrhage. The standard immunotherapy for Goodpasture's disease is cyclophosphamide, but due to known reproductive toxicities associated with cyclophosphamide and the patient's age, it was decided to use alternate but less studied therapies for treatment. At discharge, the patient had undergone five plasmapheresis treatments, had received two doses of Rituximab with a steroid taper, and his antiglomerular basement membrane level had decreased significantly.